Exploring the textural characteristics of foods preferred by Chinese elderly individuals based on IDDSI levels - Muxi Chen; Yi Cheng; Wen Hu; Mengyan Wang; Juan Duan; Lei Shi (PLoS ONE, 2025)
Objective This study aimed to investigate the textural characteristics of foods preferred by elderly Chinese individuals and their suitability based on the International Dysphagia Diet Standardization Initiative (IDDSI) framework. The goal was to provide objective data to support the development of safe and nutritious diets tailored to the swallowing abilities of the elderly. Methods A cross-sectional observational study was conducted, using web-scraping technology to identify 26 commonly preferred food ingredients among elderly individuals across seven regions of China. These foods were prepared and evaluated according to IDDSI levels 0–7. Texture analysis was performed to measure hardness, cohesiveness, and adhesiveness, with statistical tests including chi-square analysis and multiple linear regression used to explore the relationships between these textural properties and IDDSI levels. Results As IDDSI levels increased, the hardness of various food categories generally showed an upward trend, with significant increases observed in fruits, vegetables, grains, and tubers at IDDSI levels 6–7 (p≤0.05). Cohesiveness varied without a clear linear trend, showing significant changes at specific IDDSI levels for meats, grains, and tubers (p≤0.05). Adhesiveness initially increased and then decreased across the IDDSI spectrum, with the most significant fluctuations occurring in mixed beans, fruits, and grains at levels 5–7 (p≤0.05). Regression analysis revealed that cohesiveness had the most substantial impact on IDDSI levels (coefficient = -5.224, p≤0.05), followed by adhesiveness (coefficient = -0.021, p≤0.05), and hardness (coefficient = 0.002, p≤0.05). Conclusion The findings underscore the importance of considering the textural properties of foods when designing diets for elderly individuals with dysphagia. The study provides empirical evidence supporting the IDDSI framework and offers a predictive model that can assist in the development of customized diets, ensuring both safety and nutritional adequacy. Future research should focus on refining food preparation methods to better meet the specific needs of this population.